Research on Web Service Composition Algorithm Using Description Logic - Yuemin Wang (Institute of Advanced Engineering and Science, 2014)
This paper presents a dynamic Web service composition algorithm based on description logic. Firstly, each input or output of the Web service request is regarded as a concept of description logic and according to the semantic similarity between concepts given the five types of description logic, we study on the dynamic composition algorithm based on service. Because the factors of service semantics and quality of service composition are considered, the algorithm can automatically implement dynamic composition according to the user's service request. Because of using the expression ability of semantic description logic, when Web service is combined the algorithm can determine whether the service can be combined according to thesemantic relationship between concepts, thus the probability of successful combination can be improved. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3536